A Comparison of 4% Succinylated Gelatin Solution versus Normal Saline in Stable Normovolaemic Sheep: Global Haemodynamic, Regional Blood Flow and Oxygen Delivery Effects - Wan, L.; Bellomo, R.; May, C. N. (Anaesthesia and intensive care, 2007)
The objective of this study was to compare the effects on regional blood flow and regional oxygen delivery of 4% succinylated gelatin solution (Gelofusine®, B. Braun) with those of normal saline. This was a randomised, controlled, crossover large animal study, which took place at the animal laboratory of university physiology institute. The subjects were seven merino cross-ewes. We implanted flow probes around the aorta, coronary, renal and mesenteric arteries. We randomised animals to observation (control), normal saline (one litre over 15 minutes) or Gelofusine * (one litre over 15 minutes). We measured central haemodynamics, organ blood flows, arterial blood gases and haemoglobin every 30 minutes for 210 minutes. Compared to control, both Gelofusine * and normal saline significantly and similarly increased mean arterial pressure, stroke volume, cardiac output and central venous pressure in the first hour (P <0.05). Such changes, however, were transient except for the increase in cardiac output seen with Gelofusine®. Normal saline significantly increased mesenteric blood flow in the first hour (P <0.05), while Gelofusine * caused a specific, sustained and progressive increase in renal blood flow and conductance (P <0.05). Both fluids increased urine output and creatinine clearance (P <0.05), but, due to haemodilution, both decreased renal oxygen delivery in the first hour (P <0.05). Normal saline and Gelofusine® have transient, volume expansion-related systemic haemodynamic effects, which are greater for Gelofusine®. Saline had a more pronounced early effect on mesenteric blood flow, while Gelofusine * had a sustained and progressive greater effect on renal blood flow. The transient increase in urine output and creatinine clearance seen with both fluids occurred while renal oxygen delivery decreased.